Beyond Mere Presence: Gender Norms in Oral Arguments at the U.S. Supreme Court. (September 2020) - Gleason, Shane A.
Women are less successful than their male counterparts at Supreme Court oral arguments under certain circumstances. However, existing work relies on mere presence rather than on any action female attorneys take in their argument. Drawing on recent work that stresses gender is performative, I argue success for women at oral arguments is tied to conformance with gender norms, subtle and unconscious expectations of how men and women should communicate. Via a quantitative textual analysis of the 2004–2016 terms, I find attorneys are more successful when their oral arguments are more consistent with gender norms. Specifically, male attorneys are rewarded for using less emotional language whereas female attorneys are successful when using more emotional language. This study represents a more nuanced and performative understanding of gender at oral arguments. These results raise normative concerns about how effective women are at the Supreme Court.